Effect of Prebiotics Supplementation on Growth Performance and Blood Biochemical Parameters in Commercial Broiler - Moilwa, Mpho Nametso (Indian Journal of Animal Nutrition, 2021)
The present study was undertaken to evaluate the effect of supplementing different levels of prebiotic i.e. mannan oligosaccharide (MOS) on growth performance and blood biochemical parameters on commercial broiler chickens. One hundred and sixty day-old broiler chicks (Cobb 400) were randomly assigned to four dietary treatments (control (T1), 0.1%, 0.25% and 0.5% supplementation of MOS in groups T2, T3 and T4, respectively). Each treatment was replicated four times with 10 birds/replicate. Growth performance e.g., feedintake, body weight gain, feed conversion ratio were observed. Blood biochemical parameters were observed by sacrificing four birds per group at the end of the trial. Weekly body weight gain was found to increase significantly (P